Technostress in students and quality of online learning: role of instructor and university support - Saleem, Farida; Chikhaoui, Emna; Malik, Muhammad Imran (Frontiers in Education, 2024)
Online learning provides flexibility and convenience to students, however, it also presents various challenges, such as technostress. Technostress is the psychological discomfort or stress experienced by individuals due to the use of technology, particularly when they cannot cope with its demands. Students’ technostress levels can have a negative impact on their online learning experiences. Drawing from the Community of Inquiry (CoI) framework, the study investigates the moderating impact of instructor and university support on technostress and the quality of online learning relationship in university students. Data were collected from 392 university students taking one or more online courses. Results reveal that technostress has a negative impact on the quality of online learning. However, this negative impact is mitigated in the presence of support from the instructor and the university separately and jointly. The study makes an important contribution to the growing body of knowledge by identifying instructor support and university support as important contributors to the communities of inquiry in an online educational setting.